KONSISTENSI KONSTITUSI INDONESIA DALAM PELAKSANAAN JUDICIAL REVIEW UNDANG-UNDANG - Jun Mawalidin (Prodi Tata Negara (Siyasah) IAIN Langsa, 2021)
The author in the observation of research studies on the constitusional court in Indonesia runs on the basis of government regulations and the 1945 constitution. The constitutional court, which was established since 2003, has proven its usefulnes and role in safeguarding the constitution and state ideology. All efforts and Ijtihad carried out by MK are solely for the sake of upholding social justice for all Indonesian people. The birth of the Indonesian constitution began during the independence period complied by the preparatory body for Indonesia’s independence efforts (BPUPKI). The existence of the Constitutional Court in revising a law or other government regulation is a force for society to fight and seek justice for regulations. The Constitutional Court has reviewed the laws governing its authority dozens of times the Constitutional court’s decision has left pros and cons. Judicial Review of laws in Indonesia can be carried out by the supreme court and the Constitutional court, however, the theory and laws are different.